Sensory aspects and dietary selectivity of children with autism spectrum disorder: an integrative review study (Research, Society and Development, 2021)
Introduction: Autism Spectrum Disorder (ASD) is considered a neurodevelopmental disorder that affects social communication and behaviors, which are restricted, persistent or stereotyped, including changes in sensory processing, in a hypo- or hyper-reactive way. These sensory dysfunctions can cause feeding problems, and the most cited food selectivity is common to children with ASD, where it is determined by food rejection, resistance to the new, and limitation in the food repertoire. Objective: To identify sensory aspects and their interference in food selectivity of children with Autism Spectrum Disorder. Methods: It consists of an integrative review, using the following electronic databases: Lilacs (Literaturac Latino-Americana e do Caribe em Ciências da Saúde), Pubmed (U.S. National Library of Medicine) and Scielo (Scientific Electronic Library Online) by crossing the following descriptors, in Portuguese and English: Food selectivity/ Food Fussiness; Feeding Behavior/Autism Disorder; Autism Spectrum Disorder/Autism Spectrum Disorder; Autism/Autism; Autism/Autistic Disorder, using the Boolean operator AND. Results: A universe of 818 articles was obtained, after the eligible criteria 39 articles were selected. Finally, after reading the full articles, it resulted in 9 articles composing the study. Conclusion: The scientific literature demonstrates that children with Autism Spectrum Disorder present sensory alterations, such as: oral sensory sensitivity, tactile and olfactory. With the consequence of greater food refusals. However, few articles are found.